Effect of Tris(1,3-Dichloroisopropyl) Phosphate as Flame Retardant on Mechanical Properties and Fire Resistivity of PU Composites - Redwan, Amamer Musbah; Badri, Khairiah Haji; Baharum, Azizah (Al-Nahrain Journal of Science, 2019)
Palm oil based polyurethane composites that are reinforced with Tris(1,3- dichloroisopropyl) phosphate TDCPP which function as flame retardants (FR) at different proportions of 3, 6 and 9% were synthesized. The polyurethane composite’s influence on the mechanical (tensile strength, impact and flexural limits and modulus) and thermal characteristics (fire test) of the polyurethane composites were examined. Increased loading of TCPP resulted in increased hardness (up to 39%) which translates to a marginal increase in Shore D hardness as the TDCPP content increases. With higher TDCPP loading, the impact and flexural capabilities decreased because of the fragile interfacial bonding between the TDCPP and PU matrix. Loading of 3%, 6% and 9% of TDCPP resulted in the decrease of impact strength by 25%, 24% and 23% respectively. Lowest flexural ability (at a reduction of 21%) was exhibited with the highest amount of TDCPP loading (9%) and the modulus had decreased by 23%. When the percentage of TDCPP loading increased, this resulted in a lower heat of combustion of the composites which manifested in the form of lower burning rate from 5.4 mm/s to 2.7 mm/s in the fire test operated.